2016
DOI: 10.1371/journal.pone.0161674
|View full text |Cite
|
Sign up to set email alerts
|

Is Beta Radiation Better than 5 Flurouracil as an Adjunct for Trabeculectomy Surgery When Combined with Cataract Surgery? A Randomised Controlled Trial

Abstract: IntroductionIn an African setting surgery is generally accepted as the treatment of first choice for glaucoma. A problem with trabeculectomy surgery for the glaucomas is the frequent co-existence and exacerbation of cataract. We report a randomized controlled trial to compare the use of beta radiation with 5FU in combined cataract and glaucoma surgery.Participants and MethodsConsenting adults aged >40 years with glaucoma, an IOP>21mmHG and cataract were enrolled and randomised to receive either 1000cG β radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In reporting the severity of adverse events, two large multicenter trials defined sight threatening complications as loss of at least 2 lines of Snellen VA or return to the operating room. 1,2,3,26,27,28 Five studies provided definitions of major, devastating or severe complications in their methodology 1,2,3,26,27,28,34,45,48 or attempted to give examples of them 16,17 . The different descriptions of severe or major complications are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In reporting the severity of adverse events, two large multicenter trials defined sight threatening complications as loss of at least 2 lines of Snellen VA or return to the operating room. 1,2,3,26,27,28 Five studies provided definitions of major, devastating or severe complications in their methodology 1,2,3,26,27,28,34,45,48 or attempted to give examples of them 16,17 . The different descriptions of severe or major complications are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the PTT are published elsewhere 12. In summary, patients with primary open angle glaucoma and cataract fulfilling the inclusion criteria (table 2) were recruited in the PTT.…”
Section: Methodsmentioning
confidence: 99%
“…Each enrolled patient underwent PT on the eye with better VA with random allocation to receive either adjunctive 5FU or beta radiation at the time of surgery 12. In a number of patients enrolled in the trial, phacoemulsification with intraocular lens (IOL) implant alone was subsequently performed in the fellow eye.…”
Section: Methodsmentioning
confidence: 99%
“…However, the β-radiation group had a higher risk of cataract [32], but this may have been associated with lower pressures which is less often seen with newer GFS such as the Moorfields Safer surgery System [6]. When β-radiation was compared with intraoperative 5-FU, there was no difference in risk of failure or complication following phacotrabeculectomy [33]. More recently, randomised trials have shown that β-radiation with MMC are superior to MMC alone [34].…”
Section: Therapies Targeting Proliferationmentioning
confidence: 99%